Unexpected effect of citrate ions on the corrosion process of carbon steel in alkaline solutions - Toujas, S. (2017)
The effect of citrate ions on the passive film stability on carbon steel, at pH 13, was evaluated. The study involved cyclic voltammograms, potentiodynamic polarization curves, micro-Raman spectroscopy and weight-loss tests. No beneficial effects on delaying or inhibiting pitting were observed in the presence of citrate ions. Organic compounds with carboxylate groups are promising corrosion inhibitors. However, the incorporation of citrate ions is clearly harmful to carbon steel in alkaline solutions and accelerates the corrosion process. Citrate ions adsorption is not observed on passive steel. Instead, citrate ions can unexpectedly dissolve the passive layer facilitating the corrosion process.